2022
DOI: 10.3390/ijms231911770
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced BDNF and TrkB Activation Enhance GABA Neurotransmission in Cerebellum in Hyperammonemia

Abstract: Background: Hyperammonemia is a main contributor to minimal hepatic encephalopathy (MHE) in cirrhotic patients. Hyperammonemic rats reproduce the motor incoordination of MHE patients, which is due to enhanced GABAergic neurotransmission in the cerebellum as a consequence of neuroinflammation. In hyperammonemic rats, neuroinflammation increases BDNF by activating the TNFR1–S1PR2–CCR2 pathway. (1) Identify mechanisms enhancing GABAergic neurotransmission in hyperammonemia; (2) assess the role of enhanced activat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 77 publications
2
17
0
Order By: Relevance
“…In the cerebellum of hyperammonemic rats, increased TNFα levels and activation of its receptor TNFR1 increase the pro‐inflammatory cytokine IL‐1β, glutaminase, and HMGB1 and enhances GABAergic neurotransmission by increasing GAD67, altering the content of GABA transporters GAT1 and GAT3 and increasing the content of GABA A receptor subunits. This enhanced GABAergic neurotransmission is responsible for motor incoordination and impairment of locomotor gait 32,37–39 . A similar process would occur in the cerebellum of BDL rats and reduction of TNFα in the cerebellum by golexanolone would contribute to the reduction of proinflammatory factors and of GABAergic neurotransmission.…”
Section: Discussionmentioning
confidence: 90%
“…In the cerebellum of hyperammonemic rats, increased TNFα levels and activation of its receptor TNFR1 increase the pro‐inflammatory cytokine IL‐1β, glutaminase, and HMGB1 and enhances GABAergic neurotransmission by increasing GAD67, altering the content of GABA transporters GAT1 and GAT3 and increasing the content of GABA A receptor subunits. This enhanced GABAergic neurotransmission is responsible for motor incoordination and impairment of locomotor gait 32,37–39 . A similar process would occur in the cerebellum of BDL rats and reduction of TNFα in the cerebellum by golexanolone would contribute to the reduction of proinflammatory factors and of GABAergic neurotransmission.…”
Section: Discussionmentioning
confidence: 90%
“…Specifically, it boosts serotonin synthesis by upregulating tryptophan hydroxylase, a key enzyme involved in serotonin production. , Additionally, serotonin and dopamine increase BDNF levels by binding to the TrkB receptor, leading to an increase in BDNF gene expression. , This aligns with the finding that selective serotonin reuptake inhibitors (SSRIs) activate BDNF-TrkB signaling. A recent study demonstrated that activating BDNF signaling induces an increase in GABAergic transmission and GABA levels. Specifically, heightened BDNF and TrkB activation led to the upregulation of membrane expressions of GABA. Conversely, a reduction in the level of BDNF resulted in the dysregulation of GABAergic transmission, leading to an imbalance in excitatory and inhibitory neurotransmission. This reduction of BDNF and the subsequent dysregulation of GABAergic transmission are recognized as major mechanisms in neurodegenerative processes. LB-GABA protects neurons from oxidative-stress-induced cell damage, thereby enhancing cell viability (Figure ).…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, heightened BDNF and TrkB activation led to the upregulation of membrane expressions of GABA. 59 Conversely, a reduction in the level of BDNF resulted in the dysregulation of GABAergic transmission, leading to an imbalance in excitatory and inhibitory neurotransmission. This reduction of BDNF and the subsequent dysregulation of GABAergic transmission are recognized as major mechanisms in neurodegenerative processes.…”
Section: Discussionmentioning
confidence: 99%
“…However, our model does not recapitulate a situation of hyperammonaemia added to the presence of liver disease for which bile duct ligation, for example, may be a more appropriate choice. On the other hand, the definition of the role of hyperammonaemia per se in the pathogenesis of sleep–wake abnormalities may help to start shedding light on the complex interactions between hyperammonaemia, liver synthetic dysfunction, enhanced GABAergic tone, 57 systemic inflammation, 58 neuroinflammation 59 and portal‐systemic shunting on the overall sleep–wake phenotype exhibited by patients with cirrhosis. Of interest, GABAergic tone modulation was recently shown to reduce subjective sleepiness and electroencephalographic slowing in patients with cirrhosis and mild HE, 60 possibly leading to the hypothesis that the glutamate/GABA neurotransmission imbalance which is thought to underpin HE 61,62 may have cumulative, negative effects on both the neuronal and astrocytic components of the master clock.…”
Section: Discussionmentioning
confidence: 99%